Adoption of Coccidiosis Vaccines by Poultry Farmers in Ijebu Area of Ogun State, Nigeria - Oladoja, M.A.; Olusanya, T.P. (International Journal of Poultry Science, 2007)
The paper focused on adoption of coccidiosis vaccines by poultry farmers in Ijebu-Area of Ogun State, Nigeria. Specifically, the poultry farmers selected personal characteristics such as age, sex, religion, marital status, educational attainment, farm income and sources of credit were identified Their level of awareness and adoption of the coccidiosis vaccines were also determined. The relationship between adoption and the selected personal characteristics was established. The relationship between adoption and constraints to adoption was also established. Eighty eight (88) poultry farmers were selected through a stratified sampling method from six (06) local government councils using a pre-tested Questionnaire. Examination of the poultry farmer's personal characteristics revealed that 80.7 percent were male and is between age-range of thirty-one and fifty years. Sixty seven (67) percent were Christians while 98.9 percent had formal education. Almost forty one percent (40.9%) reared between 500 and 1000 birds while 29.5 percent reared above 1000 birds with farm income ranging from 25,000 to above N50, 000 per month. 88.6% are aware of coccidiosis vaccines, 83 percent had adopted and immuncox® is the most commonly used (66.2%). The study revealed that age and sex were significantly related to adoption amongst other personal characteristics tested. The study also revealed that there is no significant relationship between adoption and constraints to adoption. Coccidiosis vaccines were found to have gained widespread acceptance among poultry farmers in Ijebu area of Ogun State, Nigeria. It was recommended that Unified Extension Agents in the area should facilitate the transfer of the technology and dissemination of information on coccidiosis vaccines to both small and medium poultry farmers in the study areas. There should also be effective extension services to small-scale commercial poultry farmers will enhance their productivity and eventually elevate them to large-scale level of production.